THE EFFECTIVE TAHFIZ LEARNING MODEL APPLIED BY FAMILIES IN BANDA ACEH AND ACEH BESAR, INDONESIA - Fithriani Fithriani (Universitas Islam Negeri Ar-Raniry, 2022)
The Qur'an is one of the miracles of Allah bestowed to the Prophet Muhammad (Peace be upon him-PBUH). As a miracle, its authenticity will be maintained until the end of time. One way to maintain the purity of the Qur'an is by memorizing it. Recently, either children or adults have been enthusiastic about memorizing the Qur'an, as proven by the opening of tahfiz schools by the government, society, or private educational institutions. The high interest in memorizing the Qur'an is God's guidance to maintain the purity of His words. On the other hand, parents also play a significant role in encouraging their children to memorize the Qur'an. Interestingly, although busy with work and the heads of the family or housewives, parents in Banda Aceh have successfully educated their children to become hafiz and hafizah. This qualitative study aimed to investigate the tahfiz learning model applied by families in Banda Aceh, Indonesia, to investigate the tahfiz learning model applied by families. The data was collected by observing and interviewing four hafiz families in Banda Aceh as research samples. The study results revealed that the tahfīẓ learning methods used by hafiz families were talaqqī, tasmī', tikrāri, and murāja'ah. The techniques used were ifrādi, tsawāb wa iqāb, and uswah. To conclude, The effective tahfiz learning model applied in Banda Aceh families was طريقة تكاملية (integrated method).